2015
DOI: 10.1007/s00592-015-0815-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationships between type 2 diabetes status, glycemic control, and neuroimaging measures in the Diabetes Heart Study Mind

Abstract: Aims To examine the relationships between type 2 diabetes (T2D) status, glycemic control, and T2D duration with magnetic resonance imaging (MRI)-derived neuroimaging measures in European Americans from the Diabetes Heart Study (DHS) Mind cohort. Methods Relationships were examined using marginal models with generalized estimating equations in 784 participants from 514 DHS Mind families. Fasting plasma glucose, glycated hemoglobin, and diabetes duration were analyzed in 682 participants with T2D. Models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
1
27
1
Order By: Relevance
“…Currently, age and hypertension are considered to be consistent risk factors for WMHs. Studies have shown that diabetic subjects are more prone to having more and larger WMHs than non-diabetic subjects (2)(3)(4)(5). A recent review by Del Bene et al more firmly emphasized the relationship between type 2 diabetes and both the presence and severity of WMHs, although the underlying mechanism is still not fully understood (6).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, age and hypertension are considered to be consistent risk factors for WMHs. Studies have shown that diabetic subjects are more prone to having more and larger WMHs than non-diabetic subjects (2)(3)(4)(5). A recent review by Del Bene et al more firmly emphasized the relationship between type 2 diabetes and both the presence and severity of WMHs, although the underlying mechanism is still not fully understood (6).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have obtained conflicting results regarding the associations between glucose indices and WMH. One study found that higher HbA1c levels were associated with WMH ( Schneider et al, 2017 ), while other studies did not find such an association ( Exalto et al, 2014 ; Raffield et al, 2016 ). These controversies may result from a failure to capture daily glucose variability.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that diabetes is associated with global and regional brain atrophy ( Falvey et al, 2013 ; Moran et al, 2013 ; Hirabayashi et al, 2016 ; Raffield et al, 2016 ; Schneider et al, 2017 ). The results of our study extend current observations and clearly demonstrate that postprandial hyperglycemia is independently associated with global brain atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies on T2D patients have found that diabetes [3,11] and renal [9,14] disease measures are associated with volumes of certain neuroanatomical structures, however the relationship between diabetes and the perfusion of the brain parenchyma has remained largely unknown. Additionally, according to the U.S. Center for Disease Control, African American adults are about twice as likely to be diagnosed with diabetes as European Americans [2].…”
Section: Introductionmentioning
confidence: 99%